Evaluasi Tingkat Kesesuaian Lahan Permukiman, Tambak dan Konservasi menggunakan Metode Spatial Multy Criteria Analysis - Andin Risdayanti; Mukti Ali; Ihsan Ihsan (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2017)
Based on the White Book data, in the Jeneponto district there is the potential for mangrove forests, which are spread over the Bangkala and Tamalatea Districts with a total area of ​​206 ha. Many of the mangrove forests in this region have been converted into ponds and settlements. Conversion of mangrove forests for aquaculture, settlements, ports, recreational / tourist attractions, industrial estates or other uses has a tremendous impact on the ecosystem of coastal areas. Determination of suitability of residential land, ponds and conservation is one of the efforts that can be done to prevent and control land use that is not in accordance with its designation. The purpose of this study is to identify the characteristics of existing coastal areas to analyze the suitability of residential land, ponds and conservation in the coastal areas of Bangkala and Tamalatea Districts. This study uses the Spatial Multi Criteria Analysis (SMCA) method to assess the suitability of residential land, ponds and conservation. The results showed that residential areas are scattered in coastal areas and coastal borders covering an area of ​​498 hectares, generally embankment areas are salt ponds covering 792 hectares, and conservation areas covering 639.5 hectares. The most suitable land for settlement areas is located in Bontorannu Sub-district, while the most suitable land for tambak area is located in Bontotangnga Sub-district and the most suitable land for conservation area is located in West Tonrokassi Sub-District.